2020
DOI: 10.4085/1062-6050-132-19
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health Demographics of Female Collegiate Rowers

Abstract: Context Limited information exists about health patterns among female rowers at the collegiate level. Furthermore, the element of weight class (lightweights classified as <130 lb [59 kg]) as a factor in the physical and mental health of female collegiate athletes has not been investigated, despite weight requirements in sport being a risk factor for the female athlete triad. Objective To test the hypotheses that (1) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…On average, measures of height and weight were similar to those found in a previous study looking at demographics of female collegiate rowers [26]. Previous research has shown larger (height and weight) rowers tend to be faster [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…On average, measures of height and weight were similar to those found in a previous study looking at demographics of female collegiate rowers [26]. Previous research has shown larger (height and weight) rowers tend to be faster [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…This questionnaire measured Triad risk in triathletes, where 24% ( n = 75) indicated at least one Triad component, and 8% ( n = 25) all components [ 58 ]. Another study used part of this questionnaire (presence of eating disorder, dietary habits, worrying about weight/ body image) to measure the energy-deficiency component of the Triad in female collegiate rowers [ 59 ]. The energy deficiency related components did not differ between lightweight and openweight rowers, albeit the study hypothesised that lightweight rowers appear to be at higher risk of the Triad.…”
Section: Resultsmentioning
confidence: 99%
“…Introjected, identified regulation [ 60 , 107 ]. Positive affect, emotions, feelings [ 6 , 32 , 33 , 46 , 60 , 94 , 103 , 106 , 110 , 112 ]. Self-esteem, competence, worth [ 4 , 39 , 55 , 58 , 59 , 68 , 91 , 96 , 107 , 110 , 111 , 119 ].…”
Section: Figurementioning
confidence: 99%